Understanding the regulation of vertebrate hematopoiesis and blood disorders – big lessons from a small fish. Issue 22 (25th September 2016) - Robertson, Anne L.; Avagyan, Serine; Gansner, John M.; Zon, Leonard I.
Abstract : Hematopoietic stem cells (HSCs) give rise to all differentiated blood cells. Understanding the mechanisms that regulate self‐renewal and lineage specification of HSCs is key for developing treatments for many human diseases. Zebrafish have emerged as an excellent model for studying vertebrate hematopoiesis. This review will highlight the unique strengths of zebrafish and important findings that have emerged from studies of blood development and disorders using this system. We discuss recent advances in our understanding of hematopoiesis, including the origin of HSCs, molecular control of their development, and key signaling pathways involved in their regulation. We highlight significant findings from zebrafish models of blood disorders and discuss their application for investigating stem cell dysfunction in disease and for the development of new therapeutics. Abstract :